The Innate Immune cGAS-STING-Pathway in Cardiovascular Diseases – A Mini Review - Rech, Lavinia; Rainer, Peter P. (Frontiers in Cardiovascular Medicine, 2021)
Inflammation plays a central role in cardiovascular diseases (CVD). One pathway under investigation is the innate immune DNA sensor cyclic GMP-AMP synthase (cGAS) and its downstream receptor stimulator of interferon genes (STING). cGAS-STING upregulates type I interferons in response to pathogens. Recent studies show that also self-DNA may activate cGAS-STING, for instance, DNA released from nuclei or mitochondria during obesity or myocardial infarction. Here, we focus on emerging evidence describing the interaction of cGAS-STING with cardiovascular risk factors and disease. We also touch on translational therapeutic opportunities and potential further investigations.